2014
DOI: 10.21608/scvmj.2014.65806
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among Campylobacter isolates from poultry and human of different localities in Egypt

Abstract: The present study was carried out to screen and analyze the characteristics of antibiotic resistance in Campylobacter strains isolated frompoultry and human in the poultry farms of different localities in Egypt. A total of 340 samples were taken from poultry and human from poultry farms and examined bacteriologically for isolation of Campylobacter organisms. Fifty-six (16.47%) samples were identified as Campylobacter-positive; 50 (14.71%) from poultry samples and 6(1.76%) from human samples using conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although campylobacteriosis is endemic in Egypt and considered a major cause for pediatric diarrhea [135], fluoroquinolone and macrolide resistance, was recently documented to increase in the isolated strains in Egypt [136][137][138][139][140][141][142][143][144][145][146][147]. In the period from 1991 to 2016, several studies screened and analyzed the resistance pattern of macrolides and FQ in campylobacters, especially C. jejuni and C. coli, in chickens and humans in several Governorates in Egypt as shown in Tables 2 and 3 [136][137][138][139][140][141][142][143][144][145][146][147]. Putnam [137] analyzed the annual prevalence of macrolides resistance rate in Cairo from 1995 till 2000, which was 0%.…”
Section: Incidence Of Resistance In Egyptmentioning
confidence: 99%
See 2 more Smart Citations
“…Although campylobacteriosis is endemic in Egypt and considered a major cause for pediatric diarrhea [135], fluoroquinolone and macrolide resistance, was recently documented to increase in the isolated strains in Egypt [136][137][138][139][140][141][142][143][144][145][146][147]. In the period from 1991 to 2016, several studies screened and analyzed the resistance pattern of macrolides and FQ in campylobacters, especially C. jejuni and C. coli, in chickens and humans in several Governorates in Egypt as shown in Tables 2 and 3 [136][137][138][139][140][141][142][143][144][145][146][147]. Putnam [137] analyzed the annual prevalence of macrolides resistance rate in Cairo from 1995 till 2000, which was 0%.…”
Section: Incidence Of Resistance In Egyptmentioning
confidence: 99%
“…In 2006, marked increase in resistance level of macrolides was obviously observed in Mansoura Governorate (42.8%) by Omar [140], While, no resistance was reported in Fayoum Governorate [139]. Recently, different studies reported higher resistance rates of C. jejuni and C. coli in samples obtained from chickens and humans, 94.7% in Cairo [142], 83.3% in Zagazig [144] and 100% in Cairo, Giza, Kaliobia, Monefia, Fayoum and Zagazig [143,145]. Although the resistance rate of FQ was 0% in 1991 [136], the FQ resistance rates were early observed than macrolides [137].…”
Section: Incidence Of Resistance In Egyptmentioning
confidence: 99%
See 1 more Smart Citation